Functional cognitive disorders: identification and management. (November 2019) - Poole, Norman A.; Cope, Sarah R.; Bailey, Cate; Isaacs, Jeremy D.
SUMMARY: We review the various functional cognitive disorders (FCDs) – complaints about memory function or another cognitive process in the absence of relevant neuropathology. These are increasingly coming to the attention of psychiatrists and neurologists and FCD encompasses some newly recognised conditions in addition to classic types such as pseudodementia and psychogenic amnesia. The clinical features, neuropsychological findings and treatment are presented and discussed. LEARNING OBJECTIVES: After reading this article you will be able to: describe clinical features of FCD and how it differs from neurodegenerative causes of cognitive impairment be able to subclassify cases of FCD using the proposed nosology understand how to discuss the diagnosis with the patient and explain how the symptoms arise. DECLARATION OF INTEREST: None.